Pengaruh Kepemimpinan Kepala Sekolah Terhadap Kinerja Guru Di SD Al-Irsyad Kota Sorong - Afroh Nailil Hikmah; Fadillah Wirjaza Putri (Program Studi Pendidikan Guru Madrasah Ibtidaiyah Institut Agama Islam Negeri Sorong, 2020)
This study aims to determine 1) descriptive implementation of the leadership function by the principal; 2) descriptive teacher performance through teacher competence; 3) the influence of the principal's leadership on teacher performance at Al-Irsyad Elementary School, Sorong City. This study uses a quantitative descriptive approach with a population of all teachers at Al-Irsyad Elementary School, amounting to 30 teachers. Sampling using non-probability sampling and saturated sample techniques. Data were collected by distributing questionnaires and then analyzed by descriptive analysis and simple linear regression analysis. The results of the study stated that 1) the principal carried out the leadership function in the good category, namely 76.7%; 2) teacher performance at SD Al-Irsyad is in the moderate category, which is 59.8%; 3) Principal leadership has a positive and significant influence on teacher performance at Al-Irsyad Elementary School, Sorong City. So it can be concluded that the better the principal in carrying out his leadership function, the teacher's performance will increas